Rancang Bangun Robot Pengikut Garis Dan Pendeteksi Halangan Menggunakan Mikrokontroler AT89S51 - Sumardi, Sumardi; Setiawan, Iwan; Donnel, Hendri (Transmisi, 2008)
Recently, the electronic field develop rapidly especially in creating robotic. Many competitions have conducted to compare technology, from hobbies until robotic industries are never bored to talk. Industrially, automotive robotic needed in order to make the work more efficient, then it save cost of a production. Automotive robotic used also in entering dangerous area, that there is unable to handle by human for safety reason.In this paper, there are two automotive robotic that created, which able to follow line and stop when it detects any obstruction at front side. This robotic designed by Microcontroller AT89551, ultrasonic sensor as obstruction detector and  it also have four infrared and photodiode sensors as line detector which through by feet. Automotive robotic will run following designed line, if there is any obstruction then it will stop as long as those obstructions are there and it run again if the ultrasonic sensor do not detect obstruction anymore. By regulating PWM signal (Pulse Width Modulation) from microcontroller, then the automotive robotic can walk straightly, turn and will stop if there are any obstruction detected.From the experiment and test  which performed, robot is able to pass the turn with 60 cm of diameter, while  for movement fork  it is only perform straightly and stopped, exactly if robot finding the obstruction it can stoped in the distance 40 cm. It shows that there is lack of sensor, which used in designing, then for particular fork, robotic is only able to stop and walk straightly.Keywords: Microcontroller AT89S51, Lines Follower, Obstruction Detector